BEYOND THE BALLOT: POWER-SHARING AS A PILLAR OF DEMOCRACY IN ZANZIBAR - Ngowi , Emmanuel Joseph; Maganga, Sophia Ibrahim (Ayden International Journal of Law, Political Science, and Administration, 2025)
Since the reinstatement of the multiparty system in Zanzibar in 1992, the electoral landscape has been marred by persistent strife and violence. Each election cycle has witnessed a concerning escalation of killings, injuries, and social unrest, reflecting deep-seated tensions within the political arena. Scholars such as Minde et al. (2018) attribute this tragic situation to the unaddressed electoral practices inherent in the multiparty system. Amidst accusations and counter-accusations among competing parties, both the incumbent and opposition factions have cast doubt on the integrity of the electoral process. This pervasive atmosphere of mistrust has led to heightened demands for the establishment of a free and fair electoral framework, often through the exertion of soft and hard power tactics. Consequently, electoral violence has come to dominate the political landscape of Zanzibar, posing significant challenges to its democratic governance